The Impact of Shared Governance Over Time in a Small Community Hospital. (May 2016) - Allen-Gilliam, Jerri; Kring, Daria; Graham, Rachel; Freeman, Krystal; Swain, Sandy; Faircloth, Grace; Jenkinson, Brian
Abstract : OBJECTIVE: This study examined the impact of shared governance (SG) on the professional nursing practice environment of a small community hospital over time. BACKGROUND: Shared governance has been shown to empower nurses in direct patient care to make decisions about their practice and improve job satisfaction. No research has been found that examined the progression of SG over time in a small community hospital. METHODS: Questionnaires pertaining to the professional practice environment, perception of nursing leadership, nurse empowerment, nurse satisfaction, risk of practice errors, and comfort with evidence-based practice were administered to all nurses employed at a 149-bed community hospital in central North Carolina for 5 consecutive years. RESULTS: Results showed that nursing leadership and SG explained 90% of the variance in the nursing professional practice environment. This relationship held true for 5 years. All variables showed continued improvement for 4 years, until year 5 when the organization experienced disruptive change. Even during this year, the results did not return to baseline. CONCLUSIONS: In order to improve the professional practice environment of nurses, hospitals should focus on strong nursing leadership and a sound SG infrastructure.